Penambahan Menu Web Survei di Website Badan Perencanaan Pembangunan Daerah dan Penelitian Pengembangan Kota Samarinda - Arif Nur Rahman; Ibnu Sabdaniansyah; Muhammad Rifqi Pratama; Wawan Joko Pranoto (BADAN PENERBIT STIEPARI PRESS, 2024)
The Regional Development Planning Agency and Research and Development of Samarinda City are striving to enhance the quality of services and community participation in the planning and development processes. One proactive measure taken is the integration of a web survey menu into the institution's official website with the title